THE EDITION EFFECT OF NATURAL FIBERS ON POLYMERIC MATERIALS AND STUDY SOME OF THERMAL AND MECHANICAL PROPERTIES - Mohammed, Raghad Hussein; Hassan, Mustafa Amer; Sadeq, Noor Sabah (Al-Nahrain Journal of Science, 2010)
This research has been done by reinforcing the matrix (polyester) resin with natural material (frond palm). The fibers were exposure to chemical treatment before reinforcement.Different volume fractions were used (0%, 15%, 20%). After preparation of composite material some of the physical properties have been studied of samples preparation. They were Tensile strength test, Impact test, and Thermal conductivity. The thermal conductivity was studied, the values of thermal conductivity were increased with increasing of volume fraction of all specimens and also the tensile strength and flexural strength were decreased with increasing volume fraction of fibers, while the impact strength was increased with volume fraction 15% but with continuouity of reinforcement, the impact strength wasdecreased, and also the chemical treatment of fibers improved the mechanical and thermal properties.